Research advances on the risk of prostate cancer from phthalates exposure: from epidemiological evidence to multidimensional prevention and control - Wang, Binbin; Cao, Hongliang; Li, Shuxin; Tang, Zhijun; Huang, Gengchen; Li, Zhanhao; Ma, Yutao; Wei, Wei; Chen, Mo (Frontiers in Cell and Developmental Biology, 2026)
Prostate cancer (PCa) poses a significant threat to men’s health worldwide, with persistently high incidence and mortality rates. Phthalates (PAEs), typical environmental endocrine disruptors (EDCs), are ubiquitous in the environment and readily accumulate in the human body due to their widespread use in plastics and consumer products. Their potential role in PCa development has drawn considerable attention. This review systematically summarizes the epidemiological associations between PAEs and PCa, their potential mechanisms of action, long-term risks, and corresponding prevention and control strategies. Epidemiological studies confirm that high-molecular-weight PAEs (e.g., di(2-ethylhexyl) phthalate [DEHP], dibutyl phthalate [DBP]) are significantly associated with increased PCa risk, with abdominally obese men identified as a susceptible population. Urinary PAE metabolites (e.g., mono(2-ethylhexyl) phthalate [MEHP], mono-n-butyl phthalate [MnBP]) serve as non-invasive biomarkers for assessing PAE exposure in prostate tissue. Mechanistically, PAEs may regulate PCa progression through multiple pathways, including disrupting the androgen/estrogen signaling balance, inducing epigenetic abnormalities (DNA hypomethylation, microRNA dysregulation), activating pro-proliferative/invasive signaling pathways (MAPK/AP-1, Wnt/β-catenin pathways), and inducing oxidative stress and facilitating epithelial-mesenchymal transition (EMT). Concurrently, PAEs may pose long-term carcinogenic risks through developmental programming and synergistic interactions with obesity to exacerbate PCa risk. Furthermore, this review proposes a multi-tiered prevention and control system comprising industrial source control, targeted protection of susceptible populations, occupational safeguards, and clinical integration. Future research should focus on core scientific questions, such as identifying key PAE subtypes that may be carcinogenic to the prostate, elucidating transgenerational epigenetic mechanisms underlying PAE-induced PCa susceptibility, and verifying the reversibility of PAE-obesity interactions in PCa development, to provide more substantial evidence for mitigating PAE-associated PCa risk.